MASINGCI as an innovative snack to prevent stunting - Nurmaliah, Elsa; Ibtisamah, Nailah; Gushela, Priska Tiarany; Anjani, Shena Ravina; Ramadhani, Zakiyyah Putri; Sutrisno, Imam Tri (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Stunting is a condition in which a child experiences stunted growth. This is characterized by a height that is lower than the standard set for a certain age and gender, and stunted cognitive development in children. Stunting is a significant public health problem in Indonesia. With a prevalence that remains high, stunting is a problem that requires the involvement of multiple parties. Based on this, this community service is carried out with the aim of developing a product to reduce stunting rates, especially in Cibungur Village, Sumedang Regency. The product developed through this community service is Martabak Singkong Cibungur, also known as MASINGCI. This product is used as additional food for children. The product is introduced to the community through demonstration and counseling methods. Through the MASINGCI product, which contains carbohydrates, fiber, vitamins, and minerals, as well as a familiar taste, it is hoped that it can maximize the nutrition obtained by children, thereby helping to reduce stunting rates. In addition, through this community service approach, it is hoped that the prevalence of stunting in Cibungur Village can decrease significantly and increase public awareness of the importance of balanced nutrition for children. Abstrak Stunting merupakan kondisi anak mengalami pertumbuhan yang terhambat. Hal tersebut ditandai dengan tinggi badan yang lebih rendah dari standar yang ditetapkan untuk usia dan jenis kelamin tertentu serta terhambatnya perkembangan kognitif anak. Stunting menjadi sebuah permasalahan kesehatan masyarakat yang signifikan di Indonesia. Dengan prevalensi yang masih tinggi, stunting menjadi permasalahan yang perlu ditangani dengan melibatkan berbagai pihak. Berdasarkan hal tersebut, pengabdian ini dilaksanakan dengan tujuan mengembangkan salah satu produk untuk mengurangi angka stunting utamanya di Desa Cibungur, Kabupaten Sumedang. Produk yang dikembangkan dalam pengabdian ini adalah Martabak Singkong Cibungur atau MASINGCI. Produk ini dijadikan sebagai pemberian makanan tambahan bagi anak-anak. Produk dikenalkan kepada masyarakat melalui metode demonstrasi dan penyuluhan. Melalui produk MASINGCI yang mengandung karbohidrat, serat, vitamin dan mineral serta rasa yang tidak asing, diharapkan dapat memaksimalkan gizi yang diperoleh oleh anak-anak sehingga dapat membantu mengurangi angka stunting. Selain itu melalui pendekatan pengabdian ini, diharapkan prevalensi stunting di Desa Cibungur dapat menurun secara signifikan dan meningkatkan kesadaran masyarakat akan pentingnya keseimbangan gizi bagi anak-anak. Kata Kunci: camilan; singkong; stunting